2022
DOI: 10.3389/fresc.2021.784450
|View full text |Cite
|
Sign up to set email alerts
|

A Scoping Review of Barriers and Facilitators Affecting the Lives of People With Disabilities During COVID-19

Abstract: PurposeThis scoping review aimed to identify the barriers and facilitators to everyday activities and social participation of people with a disability (PWD) during the first wave of the COVID-19 pandemic.MethodsThe search terms (disability and COVID-19) were used in four databases: CINAHL, Medline (Ovid), EMBASE and Web of Science. The search conducted from January 2019 to September 22, 2020, identified 465 peer reviewed articles and abstracts and were screened in Covidence software. Studies were included if t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 85 publications
0
14
0
Order By: Relevance
“…For example, following recommendations from the Centers for Disease Control and Prevention (CDC) and the WHO, governments in Europe, North/South America, Africa, and Asia including 12 low-income, middle-income and high-income countries tried to reduce the duration of inpatient treatments ( 31 ). To this effect, a scoping review with studies from different countries including most commonly the US, the U.K., and Brazil, showed significant disruption to healthcare during the pandemic and worsening health outcomes in persons with disabilities ( 7 ). In Germany, the pandemic caused a reduction in the number of medical rehabilitation requests by 14.5% ( 33 ).…”
Section: Responses To Covid-19 Across the Globementioning
confidence: 99%
See 1 more Smart Citation
“…For example, following recommendations from the Centers for Disease Control and Prevention (CDC) and the WHO, governments in Europe, North/South America, Africa, and Asia including 12 low-income, middle-income and high-income countries tried to reduce the duration of inpatient treatments ( 31 ). To this effect, a scoping review with studies from different countries including most commonly the US, the U.K., and Brazil, showed significant disruption to healthcare during the pandemic and worsening health outcomes in persons with disabilities ( 7 ). In Germany, the pandemic caused a reduction in the number of medical rehabilitation requests by 14.5% ( 33 ).…”
Section: Responses To Covid-19 Across the Globementioning
confidence: 99%
“…The negative physical and mental health outcomes associated with COVID-19, stressed the importance of timely quality care for patients within vulnerable communities, including people with disabilities and other pre-existing health conditions who were at a higher risk of infection ( 14 , 15 ). Despite the barriers that emerged during the pandemic, changes to care and rehabilitation were also found to be a facilitator affecting the lives of vulnerable populations through for example new innovations ( 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…These measures often included physical distancing policies, economic lockdowns, and a rapid shift to virtual life (1). These restrictions changed the structure of everyday life for all individuals, and created a set of unique challenges for people with rare disorders (2). Rare disorders are disorders that affect less than 1:2000 individuals (3).…”
Section: Introductionmentioning
confidence: 99%
“…Some international studies have already reported increased stress and anxiety among individuals with NDCs and their families in relation to the pandemic (Iovino et al, 2021;Pettinicchio et al, 2021;Siracusano et al, 2021;Navas et al, 2022). Nevertheless, published reports have highlighted the gaps in our knowledge and the limited amount of robust and good quality research concerning COVID-19 and people with NDCs (Croft and Fraser, 2021;Doody and Keenan, 2021). The present study aims to document more of the concerns of families of children with NDCs by including a large and representative sample of the entire population of individuals with NDCs, by conducting inferential analysis to allow for predictions, by investigating the impact of family conflicts and financial concerns, and by assessing the influence of specific inclusive and protective policy measures implemented in Switzerland during the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%